The Enthalpy of Solution of Low Quartz (α-quartz) in Aqueous Hydrofluoric Acid - Kilday, Marthada V. (J Res Natl Bur Stand A Phys Chem, 1973)
An adiabatic solution calorimeter was used to measure the enthalpy of solution of the NBS Standard Reference Material No. 1654 (α-quartz or low quartz) for use as a reference standard for HF solution calorimetry. The enthalpy of solution of this material at a concentration of 5 grams in 1000 cm(3) of 24.4 weight percent HF(aq) is [Formula: see text] This value also applies to the enthalpy of solution of pure low quartz within the uncertainty limits given. The enthalpy of solution of quartz (in J · g(−1)) as a function of the temperature, T, of reaction in 24.4 weight percent HF in the range 298 to 358 K, is [Formula: see text] Thus, the average ΔCp for the reaction over the range, 298 to 358 K, is − 1.586 ± 0.025 J · g(−1) · K(−1). As a function of the concentration of HF solution in the range, 18 to 30 weight percent, [Formula: see text] From measurements of the enthalpies of solution of several samples of quartz and fused silica, the enthalpy difference between low quartz and silica glass at 298.15 K was determined to be 162.2 ± 4.9 J · g(−1) (2.330 ± 0.070 kcal · mol(−1)).